Strategic approaches for ethnic health education during the Covid-19 pandemic: a preliminary study - Darshan Singh, Sarjit Singh; Karlina, Nina; Miftah, Ahmad Zaini; Widianingsih, Ida (UKM, 2024)
The wicked problem of the Covid-19 pandemic is a challenge for every government worldwide. Handling the Covid-19 pandemic requires an effective, coordinated communication strategy, and integrated policies to encourage the public to comply with health protocols and prevent virus transmission. This study examines the interplay between policy integration, communication strategies, and cognitive dissonance during COVID-19 pandemic. Utilizing causal mechanism test and cross-tabulation analysis, it compares existing strategic communication through Covid-19 guidelines from 100 ethnic groups in Indonesia with actual virus transmission to identify the effectiveness of integrated policies and communication efforts in handling the Covid-19 pandemic. We also examine the role of policy integration, which refers to the degree of alignment and coordination among the policies and actions of different levels and sectors of government in response to Covid-19. The findings suggest that cohesive policies correlate with behavioral changes during the COVID-19 pandemic when communicated effectively. The result highlights the importance of synchronizing public health directives with clear, consistent messaging to mitigate the spread of the virus. Furthermore, future study should focus on doing a thorough examination of strategic communication techniques and their efficacy among many demographics and cultural contexts.